2009
DOI: 10.1016/j.jmb.2009.04.076
|View full text |Cite
|
Sign up to set email alerts
|

The Box H/ACA snoRNP Assembly Factor Shq1p is a Chaperone Protein Homologous to Hsp90 Cochaperones that Binds to the Cbf5p Enzyme

Abstract: Box H/ACA small nucleolar ribonucleoproteins (snoRNPs) are responsible for the formation of pseudouridine in a variety of RNAs, and are essential for ribosome biogenesis, modification of spliceosomal RNAs and telomerase stability. The mature snoRNP has been reconstituted in vitro and is composed of a single RNA and four proteins. However, snoRNP biogenesis in vivo requires multiple factors to coordinate a complex and poorly understood assembly and maturation process. Among the factors required for snoRNP bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 67 publications
(95 reference statements)
4
30
0
Order By: Relevance
“…The SSD was retained by neither construct (Fig. 1H, lanes 2,4), consistent with previous data using yeast orthologs (Godin et al 2009). This indicated that the CS domain of SHQ1, even in the presence of the SSD, required NAP57 for binding.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The SSD was retained by neither construct (Fig. 1H, lanes 2,4), consistent with previous data using yeast orthologs (Godin et al 2009). This indicated that the CS domain of SHQ1, even in the presence of the SSD, required NAP57 for binding.…”
Section: Resultssupporting
confidence: 91%
“…4D, lanes 1,2) whereas binding of the SSD was unaffected by incubation with S100 (lanes 3,4) and the CS domain alone was unable to bind (lanes 5,6), as observed previously ( Fig. 1G; Godin et al 2009;Grozdanov et al 2009b). However, when bound in trans, S100 quantitatively removed the CS domain of SHQ1 but barely impacted binding of its SSD (Fig.…”
Section: Pontin and Reptin Are Required For Shq1 Releasesupporting
confidence: 78%
See 3 more Smart Citations